Apolipoprotein E favours the blunting by high‐fat diet of prostacyclin receptor activation in the mouse aorta. (22nd July 2018) - Cheng, Yanhua; Vanhoutte, Paul M; Leung, Susan W S
Abstract : Background and Purpose: NO‐mediated, endothelium‐dependent relaxations of isolated arteries are blunted by ageing and high‐fat diets, as well as by apolipoprotein E deletion. The present study was designed to test the hypothesis that apolipoprotein E deletion impairs endothelium‐dependent responses to prostacyclin (IP) receptor activation. Experimental Approach: Five‐week‐old ApoE +/+ and ApoE −/− mice were fed normal chow or high‐fat diet for 29 weeks. The aortae were isolated for the measurements of isometric tension in Halpern–Mulvany myographs. Levels of proteins were assessed by Western blotting and immunofluorescence, and cyclic nucleotide levels byelisa . Key Results: The IP receptor agonist, iloprost, induced endothelium‐, NO‐synthase‐ and IP‐dependent relaxations in aortae of young ApoE +/+ mice. High‐fat diet favoured activation of thromboxane receptors by iloprost, causing contraction. Apolipoprotein E was present in aortae of ApoE +/+ mice, especially in endothelium. Its presence was augmented by high‐fat diet. Its deletion potentiated iloprost‐induced relaxations in aortae of young mice and prevented the blunting of this response by high‐fat diet. Levels of cAMP were higher, but those of cGMP were lower in the aorta of ApoE −/− than in ApoE +/+ mice of the same age. The levels of IP receptor protein were not different between ApoE +/+ and ApoE −/− mice. Conclusions and Implications: Iloprost induced an endothelium‐dependent relaxation in the aorta of young healthy mice which involved both the cGMP and cAMP pathways. This response was blunted by prolonged exposure to a high‐fat diet. Apolipoprotein E deletion potentiated relaxations to IP receptor activation, independently of age and diet.